2008
DOI: 10.1038/sj.ki.5002721
|View full text |Cite
|
Sign up to set email alerts
|

Liver fatty acid-binding protein as a biomarker of acute kidney injury after cardiac surgery

Abstract: Acute kidney injury (AKI) is a major complication of cardiac bypass surgery. We examined whether levels of liver fatty acid-binding protein (L-FABP) can be an early biomarker for ischemic injury by measuring this protein in the urine of 40 pediatric patients prior to and following cardiopulmonary bypass surgery. AKI was defined as a 50% increase in the serum creatinine from baseline, which was normally not seen until 24-72 h after surgery. Enzyme-linked immunosorbent assay analysis showed increased L-FABP leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
289
2
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(307 citation statements)
references
References 30 publications
7
289
2
9
Order By: Relevance
“…Given this, it has become increasingly evident that a single biomarker for AKI may not provide complete information and that simultaneous examination of other serum and urinary biomarkers may be ideal (21). Recent studies have uncovered other AKI biomarkers such as neutrophil gelatinaseassociated lipocalin (NGAL) (5), IL-18 (22), liver-type fatty acid binding protein (23), and kidney injury molecule-1 (18) in similar clinical cohorts. However, all biomarkers have their individual strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, it has become increasingly evident that a single biomarker for AKI may not provide complete information and that simultaneous examination of other serum and urinary biomarkers may be ideal (21). Recent studies have uncovered other AKI biomarkers such as neutrophil gelatinaseassociated lipocalin (NGAL) (5), IL-18 (22), liver-type fatty acid binding protein (23), and kidney injury molecule-1 (18) in similar clinical cohorts. However, all biomarkers have their individual strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…These adult data are in contrast to pediatric TRIBE AKI data (n=294), which showed no association between preoperative ACR and the development of postoperative AKI (defined as either AKIN stage 1 or a doubling of serum creatinine or receipt of renal replacement therapy [RRT]) (23). The adult ACR data represent an additional biomarker to aid in cardiac surgery AKI prediction models and supplement other recent data that point to proteinuria/albuminuria serving as a biomarker of AKI in the pre-and postoperative settings (17,24).…”
Section: Preoperative Biomarkersmentioning
confidence: 83%
“…For this reason, several blood urinary proteins have been investigated in this setting and found to serve as biomarkers of AKI after cardiac surgery, including neutrophil gelatinaseassociated lipocalin (NGAL) (10)(11)(12)(13)(14), , cystatin C (CysC) (13,16), kidney injury molecule-1 (KIM-1) (12,16), and liver fatty acid binding protein (17). Many of these previously published studies are limited in that they are small single-center studies with low severe AKI event rates (10)(11)(12)(13)(14)(15)(16)(17). However, within the last year, data from the first large international, prospective observational study investigating biomarkers after cardiac surgery have been published (18)(19)(20)(21)(22).…”
Section: Aki Associated With Cardiac Surgerymentioning
confidence: 99%
“…Neutrophil gelatinase-associated lipocalin (NGAL), N-acetyl-b-D-glucosaminidase (NAG), and liver-type fatty acid-binding protein (L-FABP) have been used as early biomarkers of renal damage in many studies, and urinary concentrations of these markers have been shown to increase, especially after hypoxia. [8][9][10] We found no studies in the literature that investigated renal damage in FS using urinary kidney injury biomarkers. Therefore, this preliminary study was planned to evaluate whether simple FS causes any renal damage detected by early kidney injury molecules, for the first time.…”
Section: Introductionmentioning
confidence: 99%